2022
DOI: 10.3390/jcm11071752
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Hospital Admissions and Healthcare Quality Indicators in Non-COVID Patients: A Retrospective Study of the First COVID-19 Year in a University Hospital in Spain

Abstract: Few studies have assessed the impact of the COVID-19 pandemic on non-COVID diseases and healthcare quality. We aimed to evaluate changes in rates of hospitalisations, complications, in-hospital mortality, and readmissions among patients with non-COVID diseases during a one-year period after the pandemic onset. From March 2018 to February 2021 a retrospective observational study of hospital admissions in a university hospital in Spain was conducted. Non-COVID hospitalisations admitted through the emergency depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
5
0
4
Order By: Relevance
“…Fourth, in our cohort we found more patients with persistent fever and seizures, which could not only be attributed to more severe clinical presentation at admission, but also reduced quality of care. More in-hospital complications -but not increasing mortality -was earlier described in non-COVID-19 patients during the first year of the pandemic [3]. Similarly, worse outcomes in 2020-2021 may also be related to hospitalrelated factors.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Fourth, in our cohort we found more patients with persistent fever and seizures, which could not only be attributed to more severe clinical presentation at admission, but also reduced quality of care. More in-hospital complications -but not increasing mortality -was earlier described in non-COVID-19 patients during the first year of the pandemic [3]. Similarly, worse outcomes in 2020-2021 may also be related to hospitalrelated factors.…”
Section: Discussionmentioning
confidence: 81%
“…
including fewer non-COVID-19 hospitalisations [3,4]. It is not known if and how the pandemic affected clinical characteristics and outcomes of specific diseases, e.g.
…”
mentioning
confidence: 99%
“…The COVID-19 pandemic led to nonurgent services for non-COVID-19 patients being postponed in some countries (13). The results of a Spanish study showed the average weekly admission rate decreased by 20.8% during the COVID-19 pandemic (14). In the present study, some vulnerable groups such as pregnant women were affected following the increasing load of COVID-19 patients, and in some cases, the lack or delay of medical services for non-coronavirus patients was reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a Danish study, Bodilsen et al 2 observed that hospital admissions for all groups of non-COVID-19 diseases decreased when compared with the periods prior to the pandemic, and, additionally, mortality rates were higher for conditions such as chronic respiratory diseases, cancer, pneumonia, and sepsis, especially during lockdown periods. Domingo et al 3 also observed a significant reduction in hospital admissions mainly related to respiratory and cardiovascular diseases in Spain.…”
mentioning
confidence: 88%